Influence of metakaolin, fly ash and nano silica on mechanical and durability properties of concrete - Kumar, R. (Trans Tech Publications Ltd, 2017)
Concrete is widely used construction material for the development of built environment which consumes huge amount of cement, around 4.3 billion metric ton all over the world. Reinforced concrete construction exposed to harsh environment such as chloride bound air causes deterioration in concrete through its pore structure by corroding the steel bar. The use of pozzolanic material i.e. metakaolin (MK), fly ash (FA), silica fume (SF), nano silica (NS) can be used as partially cement replacing material which not only reduces the pores in concrete but improves the mechanical, durability properties and microstructure of concrete. This paper reviews various transport mechanisms involved in ingress of deleterious material and incorporation of MK, FA and NS in concrete and their effects on concrete mechanical and durability properties. However, the research work provides an extended approach to evaluate combine effect using MK, FA, and NS and to produce a concrete with more refined pore structure for aggressive environment. © 2017 Trans Tech Publications, Switzerland.